Understanding the implications of government ties for nonprofit operations and functions - Zhan, Xueyong; Tang, Shui-Yan (2016)
This research explores the implications of nonprofit leaders' government ties for nonprofit operations and functions. Based on 81 survey questionnaires completed by civic environmental NGOs (eNGOs) in China and interviews with executives from 33 eNGOs, the authors examine the personal backgrounds of eNGO leaders and find that most Chinese civic eNGOs are connected with the government in one or more of three ways: political ties, service organization ties, or personal ties. Personal ties, or good guanxi with government officials, are positively associated with a higher level of funding stability and a more developed management system. Environmental NGOs with leaders who are current government officials or legislative body members are more likely to be engaged in policy advocacy. Service organization ties facilitate eNGOs' efforts to be engaged in legal services and to scale up to work on environmental issues at the national level. Moreover, an eNGO's policy advocacy engagement is associated with its ties with the nonprofit community. - Reproduced.
Keywords: Nonprofit organizations